Seychelles : Request for an Arrangement Under the Extended Fund Facility. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Seychelles' Request for an Arrangement Under the Extended Fund Facility (EFF). In the five years following the 2008 balance of payments and debt crisis, the authorities have successfully enacted a comprehensive program of reforms. Despite the success of the program, important risks and challenges remain. To face these challenges, the authorities have requested a successor EFF arrangement with the IMF. This program will help support their macroeconomic policies and protect reserve coverage over the extended period, while they carry out wide-ranging structural reforms necessary to support improvement in macroeconomic conditions, lock-in stabilization, and reduce the country's vulnerabilities.